The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1159/000443320
|View full text |Cite
|
Sign up to set email alerts
|

Severe Neonatal Anaemia, MRI Findings and Neurodevelopmental Outcome

Abstract: Background and Objective: Severe neonatal anaemia can impair cerebral oxygen supply. Data on long-term outcomes following severe neonatal anaemia are scarce. Methods: Clinical data and neurodevelopmental outcome of 49 (near) term infants with haemoglobin concentration after birth <6.0 mmol/l were retrospectively collected and analysed. In a subgroup of 28 patients, amplitude-integrated EEG was available and in 25 infants cerebral MRI was obtained. Infants were followed up at 14-35 months of age and assessed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 12 publications
2
12
0
2
Order By: Relevance
“…Moreover, they did not report their rate of mortality, which may also have accounted for differences between their and our results. In line with our results, Zonnenberg et al [13] showed normal NDOs in all surviving infants born with anemia and they suggested that neonatal anemia itself did not significantly affect the long-term outcome. Neurodevelopmental tests, however, were not routinely performed in their study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Moreover, they did not report their rate of mortality, which may also have accounted for differences between their and our results. In line with our results, Zonnenberg et al [13] showed normal NDOs in all surviving infants born with anemia and they suggested that neonatal anemia itself did not significantly affect the long-term outcome. Neurodevelopmental tests, however, were not routinely performed in their study.…”
Section: Discussionsupporting
confidence: 93%
“…Third, the cut-off value of 7 mmol/L that we chose to define perinatal anemia may also account for these positive results, because it was slightly higher compared with other studies [13,14]. The anemic group may comprise some infants who did not suffer from severe perinatal anemia.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Perinatal anemia causing HIE has been associated with higher neonatal mortality. 60,61 However, survivors of severe perinatal anemia have been also described to have reassuring neurodevelopmental outcomes at 2 to 3 years of age. 60,61 In summary, there are only limited data available on the prognostic value of biochemical parameters on neurodevelopmental outcomes.…”
Section: Anemiamentioning
confidence: 99%
“…Prenatal iron deficiency affects the normal development of brain structures, neurotransmitter systems and myelination [12]; therefore, anaemia and iron deficiency are largely demonstrated to be associated with impaired psychomotor development, impaired performance in language tests, and in motor and coordination skills [13][14][15]. DCC performed in the first minutes after birth, allows newborn, either to anaemic and nonanaemic mothers, to receive a substantial blood transfusion from placenta and increase blood volume of an average 32%, leading to obtain higher birthweight and haemoglobin concentration [8].…”
Section: Introductionmentioning
confidence: 99%